Kaposi Varicelliform Eruption in a Patient with Pemphigus Vulgaris: A Case Report and Review of the Literature - Bibisha Baaniya; Sudha Agrawal (Case Reports in Dermatological Medicine)
Haemorrhagic crusted lesions over pre-existing pemphigus vulgaris erosions should arouse suspicion of Kaposi varicelliform eruption (KVE). Immediate treatment with antivirals helps to prevent mortality and morbidities. Here, we report a case of a 67-year-old male who developed haemorrhagic crusted lesions on pre-existing pemphigus lesions during his hospital stay and obtained almost 90% resolution of cutaneous lesions of Pemphigus vulgaris as well as Kaposi varicelliform eruption within 2 weeks of acyclovir treatment along with the continuation of systemic steroids. We also highlight the review of the literature of other reported cases with its management.